Safety, pharmacokinetics, and pharmacodynamics of SHR7280, an oral gonadotropin-releasing hormone antagonist in healthy premenopausal women - Xu, Yi; Hu, Wei; Li, Jian; Jiang, Xin; Shi, Ping; Shen, Kai; Shen, Yu; Ma, Lingyu; Cao, Yu (Frontiers in Pharmacology, 2022)
Background: Treatment with gonadotropin-releasing hormone (GnRH) antagonists is a powerful strategy to suppress gonadotropin activity in women with sex hormone-dependent disorders. Herein, we provide the safety, pharmacokinetics (PK) and pharmacodynamics (PD) profiles of SHR7280, an oral non-peptide GnRH antagonist in healthy premenopausal women. Methods: In this randomized, double-blinded, placebo-controlled, dose-ascending, phase 1 trial, healthy premenopausal women were randomized to receive SHR7280 or placebo orally. Four doses of SHR7280 (200, 300, 400, and 500 mg BID) were planned. Safety, PK, and PD parameters were evaluated. Results: SHR7280 presented tolerable toxicity and most adverse events were mild in severity. SHR7280 showed rapid onset of action (median Tmax ranged from 1.0 to 1.2 h for each dose), and plasma exposure was dose-dependent. PD results showed that SHR7280 300 mg BID and above suppressed estrogen concentration within the estradiol (E2) treatment window for endometriosis (20-50 pg/mL), inhibited the emergence of the peak of luteinizing hormone (LH) and the concentration of follicle stimulating hormone (FSH), and maintained the concentration of progesterone (P) in an anovulatory state (2 nmol/L). Conclusions: SHR7280 showed favorable safety, PK, and PD profiles in the dose range of 200 to 500 mg BID in healthy premenopausal women. This study supports the continued clinical development of SHR7280 as a GnRH antagonist for sex hormone-dependent disorders in women. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT04554043